The wands of the wizarding world from the films of Harry Potter, Fantastic Beasts - Peterson, Monique,Revenson, Jody (Insight Editions, 2024)
The Wands of the Wizarding World includes thrilling insights on magical characters and wands from all 8 Harry Potter films, as well as the Fantastic Beasts series. An in-depth visual guide to the wands of the wizarding world, read detailed profiles of each wand, view stunning exclusive photography, and learn about wand statistics, insights from cast and crew, and other filmmaking secrets from the Warner Bros. archive
Keywords: Rowling; J. K.; Harry Potter; Fantastic beasts and where to find them; Rowling; J. K. / Characters; Potter; Harry / (Fictitious character) / Handbooks; manuals; etc; Magic wands; Fantastic beasts and where to find them (Motion picture) / Miscellanea; Harry Potter films / Miscellanea; Magic in motion pictures; Wizards; Witches; Hogwarts School of Witchcraft and Wizardry (Imaginary organization) / Miscellanea; Young adult literature; Illustrated works; Hexe; Magie; Verfilmung; Magier